Growth patterns of the nasolabial region following unilateral cleft lip primary repair - Xu, Yulang; Zeng, Ni; Li, Jingtao; Zheng, Qian; Shi, Bing (Frontiers in Pediatrics, 2023)
Surgical correction is the optimal way of repairing a congenital cleft lip. Patients with this condition often undergo initial surgical treatment at an early age and achieve an acceptable outcome. However, their levels of satisfaction will decrease in later stages of life as facial growth and development will inevitably cause changes in long-term outcomes, especially in the nasolabial region. Therefore, it is important for surgeons to understand nasolabial development after primary treatment and tailor their surgical techniques appropriately. This review focuses on the growth patterns of the nasolabial region after primary repair, so as to provide references for operative strategy.